A quantitative analysis infection of ovarian cyst based on examination data of computed tomography and type-B ultrasonography. Issue 1 (January 2021) - Tang, Yan; Han, Ting
Abstract: In order to explore the accuracy of computed tomography (CT) and type-B ultrasonography in the examinations infection of ovarian cyst, the computed tomography and type-B ultrasonography were used for the examinations of 50 patients with infection of ovarian cysts, whose results were analyzed to determine the accuracy. Results have shown that the misdiagnosis rates of CT for patients with infection of ovarian cyst reached 18%, in which the misdiagnosis rate of small lesion 2.1 × 1.5 × 1.8 cm was relatively higher; in addition, the misdiagnosis rates of type-B ultrasonography reached 26%, in which the misdiagnosis rate of large lesion 2.6 × 1.6 × 1.5 cm was relatively higher; however, the misdiagnosis rates of the joint examination of these methods were only 2%. In summary, the deficiencies of CT and type-B ultrasonography may lead to misdiagnosis; therefore, in the clinical practices, the examinations of patients with infection of ovarian cyst should combine CT and type-B ultrasonography together to avoid the misdiagnosis and obtain the most accurate results as much as possible, which is important to both the patients and the development of medical examinations.